From Saudi to Social Media: Arabization of Islam Via Salafi Instagram Accounts in Indonesia - Mirza Nursyabani (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
This paper argues that Salafists, through the use of social media platforms like Instagram, are not only disseminating their interpretation of Islamic teachings but also serving as representatives of the Arabization of Islam in Indonesia. In support of this argument, this research involved an ethnographic data search by randomly sampling Instagram accounts that spread Salafism and are linked with the Arabization of Islam.  The focus was specifically on the @dakwah_tauhid and @mahasiswa salaf Instagram accounts. It is argued that social media, particularly Instagram, serves as a modern platform for Salafists to propagate Islamic teachings based on the Qur’an and Sunnah. Through consistent content creation, they have garnered hundreds of thousands to a million followers, indicating their value in the Muslim community in Indonesia. Coupled with using social media like Instagram to preach ‘pure’ Islam, these accounts also function as influencers that contribute to the Arabization of Islam in Indonesia. This is evident in several aspects of their content, which emphasizes the Saudi interpretation of Islam. This includes referencing religious rulings (fatwas) issued by Saudi ulama, showcasing lectures by scholars who graduated from Saudi institutions, and promoting educational institutions in Indonesia that are managed by Saudi-trained graduates.